2014
DOI: 10.1056/nejmoa1315860
|View full text |Cite
|
Sign up to set email alerts
|

Spiroindolone KAE609 for Falciparum and Vivax Malaria

Abstract: BACKGROUND-KAE609 (cipargamin; formerly NITD609, Novartis Institute for Tropical Diseases) is a new synthetic antimalarial spiroindolone analogue with potent, dose-dependent antimalarial activity against asexual and sexual stages of Plasmodium falciparum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(202 citation statements)
references
References 13 publications
7
195
0
Order By: Relevance
“…First, the host-mediated mechanism leads to extremely rapid clearance in vivo, thus obviating the need for extended coverage. Indeed, the spiroindolones have proven faster acting in the clinic than expected from preclinical modeling (30). Second, they have exquisite selectivity due to a host-mediated mechanism-only affecting infected and treated erythrocytes.…”
Section: Clearance Ofmentioning
confidence: 99%
“…First, the host-mediated mechanism leads to extremely rapid clearance in vivo, thus obviating the need for extended coverage. Indeed, the spiroindolones have proven faster acting in the clinic than expected from preclinical modeling (30). Second, they have exquisite selectivity due to a host-mediated mechanism-only affecting infected and treated erythrocytes.…”
Section: Clearance Ofmentioning
confidence: 99%
“…The importance of identifying multistage active compounds -those that can prevent liver infection and transmission, as well as cure symptomatic blood stage infections -is becoming increasingly appreciated (8). The challenge of developing liver stage active compounds is highlighted by the recently developed spiroindolone class of antimalarial drugs, which -despite having remarkably potent blood stage killing kinetics (median parasite clearance half-life of 0.9 hours) and a potentially novel target (PfATP4) -have failed to demonstrate significant liver stage activity (24,25). One major barrier in the development of liver stage active compounds is the lack of a model system that sufficiently reproduces the complexity of human liver infection with P. falciparum.…”
Section: Discussionmentioning
confidence: 99%
“…KAE609 was safe and well tolerated in healthy subjects up to the highest tested single dose of 300 mg and the highest tested multiple dose of 150 mg daily for 3 days (Leong et al, 2014). Evaluation in 21 evaluable adult patients with uncomplicated malaria due to either P. vivax (n = 10) or P. falciparum (n = 11) showed that once-daily dosing of KAE609 at 30 mg for 3 days was well tolerated and resulted in a rapid median parasite clearance time of approximately 12 hours for both P. vivax and P. falciparum (White et al, 2014). The median fever clearance time was 8 hours and 12 hours for P. vivax and P. falciparum, respectively.…”
Section: Introductionmentioning
confidence: 99%